2019
DOI: 10.1038/s41598-019-40879-x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and epitope analysis of house dust mite allergen Der f 21

Abstract: Group 21 and 5 allergens are homologous house dust mite proteins known as mid-tier allergens. To reveal the biological function of group 21 allergens and to understand better the allergenicity of the rDer f 21 allergen, we determined the 1.5 Å crystal structure of rDer f 21 allergen from Dermatophagoides farinae. The rDer f 21 protein consists of a three helical bundle, similar to available structures of group 21 and homologous group 5 allergens. The rDer f 21 dimer forms a hydrophobic binding pocket similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
(81 reference statements)
1
13
0
Order By: Relevance
“…However, studies on the human albumins reveal that only 0.5–2 of these sites are occupied under physiological conditions suggesting that lipids bind to the shallow, surface-exposed cavities of albumins with low affinity and in rapid exchange with the solution, consistent with the physiological role of these allergens as transport proteins 3638 . In the case of the group 5 mite allergens, crystal studies of Der p 5 and its homologue Der f 21 reveal a helical bundle which can assemble into a dimeric structure, the interface of which encloses a 3000 ų cavity 39,40 . While the size of this cavity is comparable to that of Bla g 1, docking studies along with crystal structures of the related allergen Der f 21 reveal an average occupancy of only a single fatty-acid or PEG detergent molecule 39,41 .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the human albumins reveal that only 0.5–2 of these sites are occupied under physiological conditions suggesting that lipids bind to the shallow, surface-exposed cavities of albumins with low affinity and in rapid exchange with the solution, consistent with the physiological role of these allergens as transport proteins 3638 . In the case of the group 5 mite allergens, crystal studies of Der p 5 and its homologue Der f 21 reveal a helical bundle which can assemble into a dimeric structure, the interface of which encloses a 3000 ų cavity 39,40 . While the size of this cavity is comparable to that of Bla g 1, docking studies along with crystal structures of the related allergen Der f 21 reveal an average occupancy of only a single fatty-acid or PEG detergent molecule 39,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of solvent-accessible surface area (ASA) to the calculated Gly-X-Gly (GXG) tripeptide value for all the residues was obtained. Previous IgE epitope mapping of dust mite allergens from groups 5, 13, and 21 found that the major IgE-binding epitopes consist of polar and charged residues 10 , 12 , 15 , 16 . Hence, we identified all solvent-accessible, polar and charged residues (17 in total) on the surface of Der p 23, and mutated these residues to alanine to produce a set of 17 single-residue mutants.…”
Section: Resultsmentioning
confidence: 99%
“…S6 ). The immunoassay and the analysis of experimental data performed in this study have been previously used and validated in multiple other publications 12 , 15 , 16 , 25 . D56A mutant was however excluded from the analysis due to the high background in negative controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several IgE-binding studies of Bet v 1 36,37 , Der p 2 47,48 and other allergens 49,50 have revealed that the allergen-specific IgE-repertoire can be very complex in terms of IgE-clonality, affinity and concentration. Besides, it is well-known that these parameters affect effector cell degranulation, which is only triggered in the presence of at least two IgE-clones binding non-overlapping epitopes on the allergen surface 51 .…”
Section: Discussionmentioning
confidence: 99%